"Evaluation Of Air Quality By Passive And Active Sampling In An Urban City In Turkey: Current Status And Spatial Analysis Of Air Pollution Exposure " - Gaga, Eftade O.; Döğeroğlu, Tuncay; Özden, Özlem; Arı, Akif; Yay, Ozan Devrim; Altuğ, Hicran; Akyol, Nesimi; Van Doorn, Wim; ÖRNEKTEKİN, SERMİN (Springer Heidelberg, Tiergartenstrasse 17, D-69121 Heidelberg, Germany, 2012)
Concentrations of air pollutants, nitrogen dioxide (NO2), sulfur dioxide (SO2), ozone (O-3), particulate matter (PM2.5 and PM10), trace metals, and polycyclic aromatic hydrocarbons (PAHs) were measured in 2008 and 2009 in the city of EskiAYehir, central Turkey. Spatial distributions of NO2, SO2, and ozone were determined by passive sampling campaigns carried out during two different seasons with fairly large spatial coverage. A basic population exposure assessment was carried out employing Geographical Information System techniques by combining population density maps with pollutant distribution maps of NO2 and SO2. It was found that 95 % of the population is exposed to NO2 levels close to the World Health Organization guideline value. Regarding SO2, a large proportion of the population (83 %) is exposed to levels above the WHO second interim target value. Concentrations of all the pollutants showed a seasonal pattern increasing in winter period, except for ozone having higher concentrations in summer season. Daily PM10 and PM2.5 concentrations exceeded European Union limit values almost every sampling day. Toxic fractions of the measured PAHs were calculated and approximately fourfold increase was observed in winter period. Copper, Pb, Sn, As, Cd, Zn, Sb, and Se were found to be moderately to highly enriched in PM10 fraction, indicating anthropogenic input to those elements measured. Exposure assessment results indicate the need for action to reduce pollutant emissions especially in the city center. Passive sampling turns out to be a practical and economical tool for air quality assessment with large spatial coverage.
Keywords: Air pollution; Exposure assessment; Nitrogen dioxide; Sulfur dioxide; Ozone; Particulate matter; Polycyclic aromatic hydrocarbons; Geographical Information System; Hava kirliliği; maruziyet değerlendirmesi; Nitrojen dioksit; Kükürt dioksit; Ozon; Partikül madde; Polisiklik aromatik hidrokarbonlar; Coğrafi Bilgi Sistemi